ANALISIS NILAI NILAI PENDIDIKN AGAMA ISLAM DALAM FILM ANIMASI RIKO THE SERIES EPISODE 12-15 - Sulisniati (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2025)
This research discusses the values of Islamic religious education in the animated film riko the series episodes 12-15. The purpose of this study is to find out what Islamic religious education values are contained in the animated film riko the series episodes 12-15 using the theory of Imam al-Ghazali. This research is a library research. The object of this research is the analysis of the values of Islamic religious education in the animated film Riko the series episodes 12-15. The results of this author's literature study are about the analysis of the values of Islamic religious education in the animated film riko the series episodes 12-15 which are accessed through youtube riko the series. The author finds, qualitative methods and approaches, that the values of Islamic religious education found in the scenes or dialogues of the characters are moral values and worship values. Moral values include; remind each other of kindness, manners, morals to Allah, always be grateful. While the value of worship includes; Praying, praying for friends, fasting, istiqomah, saying istighfar when making mistakes, getting used to saying greetings.